The Implementation of Skimming in Developing Reading Comprehension Achievement for Students Grade V Primary School - RCL, Khadijah Khadijah (Akademika : Jurnal Teknologi Pendidikan, 2025)
Abstract Reading comprehension is a critical skill for academic success, particularly among elementary school students. This study investigates the effectiveness of the skimming technique in enhancing reading comprehension among fifth-grade students at Primary School 57 Banda Aceh. Skimming, as a reading strategy, enables students to rapidly identify key ideas and essential information within a text, facilitating better comprehension and engagement. This study was conducted using Classroom Action Research (CAR) with two cycles, incorporating planning, implementation, observation, and reflection. Data collection involved classroom observations, student assessments, and teacher reflections. The findings indicate a substantial improvement in students' reading comprehension from Cycle I to Cycle II. In Cycle I, 81.60% of students demonstrated excellent comprehension skills, with an even greater percentage of improvement observed in Cycle II, which is 93.51%. The study highlights that student who initially struggled with reading comprehension showed significant progress, as skimming enabled them to focus on critical text elements such as titles, subheadings, and key terms. Furthermore, the study emphasizes the role of effective instructional strategies in fostering reading comprehension. Teachers played a pivotal role in guiding students through skimming, ensuring that they applied the technique correctly to optimize learning outcomes. Additionally, the structured implementation of skimming contributed to increased student motivation and active participation in reading activities. The findings of this study suggest that integrating the skimming technique into language learning curricula can enhance students’ ability to process and comprehend textual information efficiently. Future research should explore the long-term effects of skimming on reading proficiency and its applicability to different text genres. Combining skimming with other reading strategies may provide a more comprehensive approach to improving students’ overall literacy skills.